The Effect of Organizational Culture and Work Flexibility on Employee Performance Mediated by Work Motivation at PT XYZ - Nataly Monica Lembang; Irwan Cahyadi; Susilo Talidobel (Business Management, 2026)
This study aims to analyze the effect of organizational culture and work flexibility on employee performance, with work motivation as a mediating variable. This research uses a quantitative approach with a causal associative design. The sample consisted of 171 respondents determined using the Slovin formula with a probability sampling technique. Data were collected through a 1–5 Likert scale questionnaire distributed electronically, and analyzed using Partial Least Square (PLS), including measurement model testing and structural model testing, as well as direct and indirect effect analysis. The results show that organizational culture has a positive and significant effect on employee performance, while work flexibility does not have a significant effect on employee performance. Organizational culture and work flexibility have a positive and significant effect on work motivation, and work motivation has a positive and significant effect on employee performance. In addition, work motivation is proven to mediate the effect of organizational culture and work flexibility on employee performance. In conclusion, improving employee performance is more effectively achieved through strengthening organizational culture and work motivation, while work flexibility contributes indirectly through work motivation.